FRI0284 Influence of Vertebral Fractures Severity and Pelvic Parameters on Global Spinal Balance in Osteoporotic Patients. (9th June 2015) - Fechtenbaum, J.; Briot, K.; Etcheto, A.; Kolta, S.; Feydy, A.; Roux, C.
Abstract : Background: Thoracic kyphosis and other postural parameters related to the postural adjustment strategy affect the biomechanical environment of the spine. These parameters can be influenced by vertebral fractures in elderly osteoporotic patients. Objectives: This study aims to compare the spine curvatures, the pelvic parameters and the global spinal balance of patients aged above 50 years with and without osteoporotic vertebral fractures. Methods: Two hundred patients (95% women) aged 66.5±13.6 years underwent a standardised lateral and antero-posterior full skeleton radiographs in the standing position, by EOS® (a low dose biplanar imaging system) in an upright weight-bearing position. VFs were evaluated according to Genant's classification and the spinal deformity index (SDI). Spinal (thoracic and lumbar Cobb's indices, thoracic tilt (T9 tilt) and lumbar tilt (L1 tilt)) and pelvic (pelvic tilt, sacral slope, and pelvic incidence) parameters were measured. Sagittal global spinal balance was measured using 3 parameters: the C7 plumb line (mm), the vertical line through the external auditory canal, and the spinosacral angle (SSA in degrees).We compared these parameters in patients with and without vertebral fracture, according to the location and the severity of VFs (SDI). We assessed the discriminative value of the global spinal parameters in patients with at least one vertebral fracture using Area Under the Curve (AUC). Results: Sixty-nine patients had at least 1 VF, with a mean number of VF of 2.3±1.7 and a mean SDI of 4.2±4.5. In patients with only lumbar VFs (N=11), only lumbar parameters (lower lumbar Cobb's angle and sacral slope and higher lumbar tilt) were modified. In contrast, in patients having only thoracic VFs (N=58), both thoracic, lumbar and pelvic parameters were different than those in patients without VFs. The greater the SDI, the greater were the thoracic Cobb's angle and pelvic tilt and the lesser the lumbar Cobb's angle. Thoracic and lumbar tilts and sacral slope were not affected by SDI increase. The global spine balance assessed by C7 plumbline and SSA was significantly altered in patients with at least one VF, and there was a dose effect of the number and severity of VFs on global spinal balance, significant for all parameters for a SDI value >2. Global spinal balance was significantly altered in patients with at least one FV and low sacral slope (113.4° vs 120.0, p=0.0012). SSA was the postural spinal parameter which better discriminates patients with at least one VF (AUC=0.706) Conclusions: Global spinal balance is significantly altered in patients with at least one vertebral fracture with a dose-effect of the number and severities of VFs. Pelvic parameters are relevant in the assessment of global spinal balance. Disclosure of Interest: None declared